Evaluación de la necromasa gruesa en tres tipos de bosque de Jenaro Herrera, Loreto - Perú - Saldaña Huayllahua, Valeria Lizet (2017)
From January to December of 2014, I stadyied the production of coarse dead wood in high terrace forest (BTA), sandwhite forest wet (BVH) and high secondary forest (BRA), by plot and transect methods. The results indicate that stock major was 16.19 t C ha-1 in high terrace forest, in sandwhite forest wet 15.27 t C ha-1 and high secondary forest 4.29 t C ha-1. The major productivity of coarse dead Wood was high terrace forest with 0.72 t C ha-1 año-1, in sandwhite forest wet 0.54 t C ha-1 año-1 and high secondary forest 0.71 t C ha-1 año-1. In adition, the BTA presented a major productivity in dry season, while BVH and BRA in rainy season. There is no relationship between productivity of coarse dead wood with the temperature and precipitation, and I conclude that between the three forests there are not significant difference in the coarse dead wood production.